Intellectual capital, isomorphic forces and internal controls over financial reporting in Ugandan microfinance institutions - Frank Kabuye; Kassim Alinda; Nicholas Bugambiro; Saphurah Kezaabu (Cogent Business & Management, 2021)
The purpose of this study is to examine the role of intellectual capital and isomorphic forces in strengthening internal controls over financial reporting (ICFR) in microfinance institutions (MFIs). This study is cross-sectional and correlational. Data were collected through a questionnaire survey of 66 MFIs that are members of the Association of Microfinance Institutions of Uganda (AMFIU). Both intellectual capital and isomorphic forces positively and significantly contribute to the strength of ICFR. In terms of control variables, ownership structure, capital structure and firm age are not significant predictors of ICFR. Policy-wise, the regulator(s) of MFIs should always issue-specific and time-bound directives to MFIs with ICFR shortfalls to enhance their control environment. Also, the responsibility of maintaining adequate ICFR should be extended to the management of MFIs by tasking them to account for lapses in ICFR. This would reduce incidences of senior management usurping the powers of the board, which would lead to overriding of ICFR. Also, policies should be specific on the composition of the board to improve its intellectual potential. To the authors' knowledge, this study provides initial empirical evidence of the influence of intellectual capital and isomorphic forces in strengthening ICFR in MFIs using evidence from a developing African country. Overall, this study found that intellectual capital (entity factor) and isomorphic forces (institutional factors) are all predictors of ICFR. This is possible because managers, employees and those charged with governance of the entity can be influenced by institutional forces that affect ICFR positively.
Keywords: 650; Internal controls over financial reporting; intellectual capital; isomorphic forces; Microfinance institutions; Uganda